Marketing Communication Strategies for MSMEs in the Digital Era : A Case Study of Culinary MSMEs in Samarinda - Muhammad Rizal; Rina Juwita; Kezia Arum Sary; Kadek Dristiana Dwivayani (International Journal of Social Sciences and Humanities, 2026)
This study examined digital marketing communication strategies employed by culinary micro, small, and medium enterprises (MSMEs) at Teras Samarinda, a riverside MSME cluster in Samarinda, East Kalimantan, Indonesia. The study aimed to analyze how these enterprises utilized digital media platforms, constructed communication messages, and engaged consumers in the context of Integrated Marketing Communication (IMC). A qualitative case study method was employed, with data collected through in – depth   interviews, direct observation, and documentation involving four MSME informants – Bebaya Mart, Gaya Ice Cream, Rustic Camp & Café, and Pedas Manis – as well as two consumer informants. The findings revealed that all four MSMEs actively used Instagram, TikTok, WhatsApp, and Facebook, primarily for brand awareness and sales conversion. Message construction varied from structured approaches using hooks and calls to action to spontaneous content creation. Consumer engagement remained largely at a responsive or interaction level rather than progressing toward long – term relational engagement. The study concluded that while digital marketing communication has positively impacted sales and consumer interest, implementation has not yet fully adhered to IMC principles of integration, consistency, and strategic sustainability. Practical and policy recommendations are provided for MSME actors, platform managers, and local government.